A clinical survey of laryngectomy patients to detect presence of the false perception of an intact larynx or the "phantom larynx" phenomenon - Pankaj Chaturvedi; Prashant V Pawar; Suhail Syed; Deepa Nair; Sourav Dutta; Devendra Chaukar; Anil K D′Cruz (Indian Journal of Medical and Paediatric Oncology)
Hypothesis: The Phantom larynx phenomenon (the false perception on an intact larynx in a laryngectomee) exists and is an important issue in the post-laryngectomy rehabilitation of such patients. Objectives: The phantom limb phenomenon has been described after amputation of a limb or other parts of the body. Amputation or removal of any part is usually associated with a global feeling that the missing part is still present. We undertook this study to identify whether a phantom larynx phenomenon actually exists in laryngectomees. We also aimed to elicit its association with the duration following surgery. Patients and Methods: We did a clinical survey of 66 post-laryngectomy patients (30-80 years of age). Twenty-two of these patients were assessed within 6 months following surgery, whereas 44 patients were assessed at least 6 months later. A questionnaire containing 11 questions was served to these laryngectomees pertaining to false perception of persistent laryngeal functions and adaptation to the post-laryngectomy status. Results: All patients showed an evidence of a phantom larynx phenomenon. In the majority of these patients, it persisted even after 6 months following surgery. There was no significant difference in the two groups (less than or more than 6 months) except for one question pertaining to occlusion of stoma for speech (77% vs. 29%). False perception of nasal breathing (59% and 43%) and olfactory sensation (63% in both groups) were the most common. Conclusion: Phantom larynx phenomenon following laryngectomy exists and may cause anxiety and poor rehabilitation among patients. Education and rehabilitation with regards to such a phenomenon is therefore needed in all patients.